Exploring Reservoir Potential of the "X Field" Offshore, Niger Delta Basin: An Emphasis on Lithofacies, Depositional Environments, and Petrophysical Characteristics - Agbasi, Okechukwu Ebuka; Esomchi, Nwokoma Uzoma; Daniel, Azunna Enyinnaya; Udoka, Ugwu Joshua (Jurnal Penelitian Fisika dan Aplikasinya (JPFA), 2023)
The geological circumstances under which sediments are built throughout time are referred to as depositional environments. The features of the sediment, such as its texture, composition, and permeability, are influenced by these depositional environments, and these qualities ultimately define the reservoir quality. This study focuses on identifying reservoirs in the western offshore region of Nigeria's Niger Delta Basin and evaluating their properties, such as lithofacies, distribution, and petrophysical characteristics like porosity and permeability, using well log analysis. By utilizing relevant and easily accessible well log data, the depositional environment and quality of the reservoir were evaluated. The data analysis involved examining gamma-ray log patterns, spontaneous potential, deep resistivity, neutron, and density. The thickness of the reservoirs varies between 15 and 440 meters, with thicker reservoirs likely being composite structures formed from layered channels. Sands deposited in high-energy settings have higher levels of porosity and permeability. Sands C and D are the most porous and permeable sand units in the field, while the remaining sands have medium permeability. Hydrocarbons are present in sands B, C, D, and E in varying fluid types and column diameters. The reservoir sands C, D, and E have high hydrocarbon saturation and low water saturation, indicating that more oil than water will be produced. On the other hand, irreducible sand B suggests that more water than oil will be produced. Reservoir sands B, C, and D contain only water and oil. This information can aid in locating production platforms and optimizing hydrocarbon recovery, as well as improving reservoir performance estimates. The geological and petrophysical data collected in this study can also guide the analysis of other fields similar to the "X Field" in Nigeria's Niger Delta offshore region.